Making space for drones: The contested reregulation of airspace in Tanzania and Rwanda. Issue 4 (4th May 2021) - Lockhart, Andy; While, Aidan; Marvin, Simon; Kovacic, Mateja; Odendaal, Nancy; Alexander, Christian
Abstract: In contrast to their use in warfare and surveillance, there is growing interest in the potential of "drones for good" to deliver societal benefits, for example by delivering medical products and other essential goods. Yet development of medical and commercial delivery has been limited globally by restrictive regulation to protect airspace safety and security. In this paper we examine how certain African countries have become testbeds for new forms of drone infrastructure and regulation, driven by the overlapping interests of governments, drone operators, and international development agencies. In particular we explore the factors that have led to the development of an advanced medical delivery network in Rwanda and contrast that with the closing down of airspace for drones in Tanzania. The paper makes a distinctive contribution to research on the ongoing constitution of dronespace as a sphere of commercial and governmental activity. Rwanda's drone delivery system is seen as the forerunner for the wider enclosure and parcelling up of the lower atmosphere into designated drone corridors that limit the democratic and disruptive potential of drone activity in line with prevailing logics of airspace regulation. Abstract : In this paper we examine how certain African countries have become testbeds for new forms of drone infrastructure and regulation, driven by the overlapping interests of governments, drone operators, and international development agencies. In particular we explore the factors that have led to the development of an advanced medical delivery network in Rwanda and contrast that with the closing down of airspace for drones in Tanzania. The paper makes a distinctive contribution to research on the ongoing constitution and enclosure of dronespace as a sphere of commercial and governmental activity.